Supply Chain Transparency: Exploring Blockchain Solutions for Enhanced Traceability and Efficiency - Khairunnisa, Novita; Christiani, Felinia; Giri Prawiyogi, Anggy (Blockchain Frontier Technology, 2024)
The increasing complexity of supply chains necessitates enhanced transparency to ensure efficiency, traceability, and trust among stakeholders. Traditional supply chain systems often struggle with issues related to data integrity, fraud, and inefficiency. This study employs a comprehensive literature review and case study analysis to investigate the implementation of blockchain technology in supply chain management. Various case studies are examined to highlight successful blockchain applications and their impact on supply chain transparency. The primary objective of this research is to explore how blockchain solutions can enhance traceability and efficiency in supply chains, ultimately leading to improved operational outcomes and stakeholder trust. Findings indicate that blockchain technology significantly improves traceability by providing immutable records of transactions and product journeys. Additionally, it enhances operational efficiency by streamlining processes, reducing costs, and minimizing the need for intermediaries. Case studies from diverse industries demonstrate practical applications and measurable benefits, including increased visibility, quicker recall processes, and enhanced accountability. The integration of blockchain technology into supply chains offers a transformative approach toachieving greater transparency and efficiency. This study highlights the potential of blockchain to address critical challenges in traditional supply chain systems and emphasizes the need for further research on scalability and interoperability to realize its full benefits.